Efficacy and safety of aspirin and rivaroxaban for venous thromboembolism prophylaxis after total hip or knee arthroplasty: A protocol for meta-analysis. Issue 49 (4th December 2020) - Le, Guoping; Yang, Chengzhi; Zhang, Ming; Xi, Licheng; Luo, Hanwen; Tang, Jingli; Zhao, Jinmin
Abstract: Background: The purpose of this meta-analysis is to compare the efficacy and safety of aspirin and rivaroxaban in the prevention of venous thromboembolism (VTE) following either total knee arthroplasty or total hip arthroplasty. Methods: A comprehensive literature search of several electronic databases (PubMed, Embase, and Web of Science) was conducted to identify relevant studies. Outcomes of interest included VTE rate, deep vein thrombosis (DVT) rate, pulmonary embolism rate, major bleeding events, mortality rate, blood transfusion, and wound complication. Risk ratio (RR) with 95% confidence intervals (95%CIs) were calculated using a fixed-effects model or random-effects model. Results: A total of 8 studies with 97, 677 patients met the inclusion criteria and were included in this meta-analysis. Compared with rivaroxaban, aspirin had a significantly higher incidence of DVT (RR = 1.48, 95%CI: 1.27, 1.72; P  < .001), and decreased risk of blood transfusion (RR = 0.94, 95%CI: 0.93, 0.94; P  < .001). However, there were no significant differences between the 2 drugs in terms of total VTE rate (RR = 1.39%, 95%CI: 0.94, 2.05; P  = .101), pulmonary embolism rate (RR = 1.64, 95%CI: 0.92, 2.92; P  = .094), mortality rate (RR = 1.13, 95%CI: 0.15, 8.27; P  = .907), major bleeding (RR = 1.00, 95%CI: 0.44, 2.27; P  = .995), and wound complication rate (RR = 0.37, 95%CI: 0.07, 1.87; P  = .229). Conclusion: Our results suggested that aspirin and rivaroxaban offered similar effect in the prevention of VTE after total knee arthroplasty or total hip arthroplasty. However, rivaroxaban seemed to have better effect than aspirin in reducing the risk of DVT, and aspirin was safer than rivaroxaban in decreasing the blood transfusion rate.